A Multi-step Usability Evaluation of a Self-Management App to Support Medication Adherence in Persons Living with HIV. (February 2019) - Beauchemin, Melissa; Gradilla, Melissa; Baik, Dawon; Cho, Hwayoung; Schnall, Rebecca
Highlights: Three-step usability evaluation using 1) traditional think-aloud protocol 2) a heuristic evaluation and 3) a cognitive walkthrough. Design issues were identified, including location and boldness of text to highlight areas of interest within the mHealth app. The mHealth app was determined to be usable overall, and these results informed updates to the app. Abstract: Purpose: Adherence to antiretroviral therapy is essential to HIV management and sustaining viral suppression. Despite simplified regimens, adherence remains difficult for certain persons living with HIV (PLWH). There is evidence to support the use of mHealth apps for effective self-management in PLWH; however, a medication adherence app with real-time monitoring for this population has not been developed and rigorously evaluated by PLWH. We developed a mHealth app (WiseApp) for HIV self-management to help PLWH self-manage their health. The purpose of this study was to evaluate the usability of the WiseApp. Methods: We conducted a three-step usability evaluation using 1) a traditional think-aloud protocol with end-users, 2) a heuristic evaluation with experts in informatics, and 3) a cognitive walkthrough with end-users. During the cognitive walkthrough, we tested two devices (fitness tracker and medication tracking bottle) that were linked to the WiseApp. Results: The think-aloud protocol informed iterative updates to the app, specifically to make it easier to see different sections of the app. The heuristic evaluation confirmed the necessity of these design changes. The cognitive walkthrough informed additional updates and confirmed that overall, the app and the linked devices were usable for the end-users. Conclusion: The results of the cognitive walkthrough with both experts and end-users informed iterative refinements to the WiseApp and finalization of a mHealth app for PLWH to better self-manage their health.